Study of Learning Attitudes and Vocabulary Mastery of Short Story Writing Skills - Rina Ari Rohmah; Ratri Isharyadi (Universitas Negeri Makassar, 2018)
This research aims to explain how great the contribution of learning attitude and vocabulary mastery towards the short story writing skills ofjunior high school students in Rokan Hulu. This research uses a quantitative approach with a descriptive method and using correlational and regression design. Stratified random sampling technique was done to select the sampel based on high, medium, and low ranking results based on national examination of the SMP2015/2016 of Rokan Hulu. The data of this research is learning attitude scale, mastery of vocabulary score, and short writing skills score.Data were analyzed using a double linear regression test, t-test, F-test, and determinant coefficient formula to determine the contribution of independent variables on the dependent variable, either single or simultaneous. Results of this study that learning attitude and vocabulary mastery either single or simultaneous contribute significantly towards the short story writing skills. Contribution of learning attitudes and vocabulary mastery simultaneously, partial contribution of learning attitudes and vocabulary mastery to the short story writing skills in a row is 36.3%, 27.9% and 31.4%.